Optimalisasi Pembelajaran Kimia Melalui Pengembangan Bahan Ajar Berupa E-Modul - Wati, Nila; Coryna Oktaviani (Chemistry Education Practice, 2025)
This research aims to optimize chemistry learning by developing teaching materials in the form of E-Modules. The E-Module is an interactive multimedia teaching material that is available online, not in print. E-Modules integrate text, images, and videos to create an engaging and interactive digital learning experience for learners. The research method employed is R&D, utilizing the ADDIE model, which focuses on the analysis stage to identify the need for developing teaching materials. The data collection techniques used were interviews, questionnaires, and documentation. The results of the interviews indicate that teachers require an interactive E-Module to enhance students' understanding of chemical materials. The results of the questionnaire analysis of the need for an integrated RADEC-based E-Module with the SETS approach on green chemical materials, with an overall average of 71.05%, are included in the criteria needed. These results highlight the importance of innovative teaching materials based on an integrated learning approach model in meeting the needs for interactivity and multimedia, thereby encouraging student involvement in learning. This study concludes that the development of RADEC-based E-Modules integrated with the SETS Approach is needed to improve the quality of chemistry learning in schools.